The breakdown of the municipality as caring platform: lessons for co-design and co-learning in the age of platform capitalism. Issue 3 (3rd July 2019) - Light, Ann; Seravalli, Anna
ABSTRACT: If municipalities were the caring platforms of the 19-20th century sharing economy, how does care manifest in civic structures of the current period? We consider how platforms – from the local initiatives of communities transforming neighbourhoods, to the city, in the form of the local authority – are involved, trusted and/or relied on the design of shared services and amenities for the public good. We use contrasting cases of interaction between local government and civil society organisations in Sweden and the UK to explore trends in public service provision. We look at how care can manifest between state and citizens and at the roles that co-design and co-learning play in developing contextually sensitive opportunities for caring platforms. In this way, we seek to learn from platforms in transition about the importance of co-learning in political and structural contexts and make recommendations for the co-design of (digital) platforms to care with and for civil society.